The Influence of Workload, Education Skills, and Autonomy on Job Satisfaction Moderated by Digital Skills - Afzil Ramadian; Awa Awa; Dede Syahrudin; Della Zulfia Nurlinda; Puput Sabrina Laelani Putri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to identify the effects of workload, education skills, and autonomy on job satisfaction, moderated by digital skills. This research is classified as quantitative research. The population of this study consists of employees at the Central Office of the Ministry of Marine Affairs and Fisheries. The sampling technique used in this study is purposive sampling, resulting in a sample size of 140 employees from the Central Office of the Ministry of Marine Affairs and Fisheries. The data analysis technique employed in this study uses Partial Least Squares (PLS). PLS is a Structural Equation Modeling (SEM) approach. The results show that: 1) Workload has a significant and positive effect on Job Satisfaction; 2) Educational Skill has a significant and positive effect on Job Satisfaction; 3) Autonomy has a significant and positive effect on Job Satisfaction; 4) Digital Skill cannot moderate the effect of Workload on Job Satisfaction; 5) Digital Skill cannot moderate the effect of Educational Skill on Job Satisfaction; and 6) Digital Skill cannot moderate the effect of Autonomy on Job Satisfaction.